Colorectal cancer - Brown, Gina; Cambridge eBooks (Cambridge : Cambridge University Press, 2007)
Colorectal cancer is the second most common cause of cancer death in the developed world. The last five years have seen dramatic improvements in the multidisciplinary management of this malignancy. In this volume, experts at the forefront of these advances contribute their knowledge and experience on the major advances that have occurred in diagnosis, staging, preoperative and adjuvant therapy, surgery and follow-up assessment of patients with this disease. Imaging underpins all aspects of the clinical management of colorectal cancer and has been shown to play a critical role in improving outcomes for patients. About the series Each volume in Contemporary Issues in Cancer Imaging - A Multidisciplinary Approach is edited by an expert guest editor, with contributions from all members of the multidisciplinary team, bringing together expertise from many specialties to promote the understanding and application of modern imaging in overall patient management.
The clinical presentation of colorectal cancer / Sarah Fisher, Ian Daniels -- Pathology for the radiologist : pathological insights / Philip Quirke -- Screening for colorectal cancer / Steve Halligan -- The surgical approach to colorectal cancer / Ian Daniels, Richard J. Heald -- Laparoscopic surgery / Anthony Antoniou, Ara Darzi -- Chemotherapy / Yu Jo Chua, David Cunningham -- Radiotherapy in colorectal cancer / Brian D.P. O'Neill, Diana M. Tait -- The changing role of endoluminal ultrasound in rectal cancer / Peter Chowdhury, Rhodri Davies, Ashley Roberts -- CT staging / Sarah Burton, Gina Brown -- MRI staging / Sarah Burton, Gina Brown -- Imaging of metastatic disease / Gina Brown -- Patterns of recurrence / Naureen Starling, Gina Brown.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Colon (Anatomy) -- Cancer; Rectum -- Cancer; Electronic books